MUATAN NILAI ISLAM DALAM PENULISAN DAN PENGAJARAN SEJARAH - Tiar Anwar Bachtiar (Department of Islamic Education, The State Islamic University Sunan Kalijaga Yogyakarta, 2015)
In History writing and teaching, objectivity can not always be realized considering the character of knowledge that created by man who always can not shy away from the “subjectivity” of a human being. Especially in the teaching of history in which every teaching must necessarily refer to the normative goals that have been set, either by the state, schools, or teachers themselves. This suggests that the normativity be the main reference in the teaching of history. Both the curriculum and the standards applied in each lesson course based on a value system that is believed by its formers respectively. The value system is what will form the miscellaneous curriculum or standards and distinguish between one to another. This study tried to view and evaluate whether the values of Islam as a religion has the largest adopted is represented well in teaching, especially in the teaching of history. Conclusions from this research that, viewed in general, the tradition of the teaching of history in Indonesia, especially in the teaching of general history, is not from Islamic traditions. Even if there are some content that do not conflict with the islamic values, its only a coincident. Especially when considering the tradition of historical writing in Indonesia intensively started from the colonial-orientalist tradition that put Islam and Muslims as their main enemy. In many cases, it is found effort to omit the role of Islam and muslim in Indonesian history, and also the historical facts about the role of Muslims that is still not seated proportionally.